Therapeutic cannabinoids in multiple sclerosis: immunomodulation revisited - Constantinescu, Cris S.; Gershkovich, Pavel (Wiley, 2018)
Cannabinoids are compounds with pleiotropic properties that act on the cannabinoid receptors, CB1 and CB2, and are divided into endocannabinoids, the endogenous ligands of these receptors, synthetic cannabinoids and phytocannabinoids. The latter are derived from the plant Cannabis sativa. The therapeutic and psychoactive properties of this plant have been observed and used for centuries. Of the over 60 compounds that are unique to Cannabis sativa, the substances that have been attributed the greatest therapeutic potential are Δ9‐ tetrahydrocannabinol (THC) and cannabidiol (CBD), both of which, used alone or combined with each other, have become approved drugs.